Understanding processes of criminalisation: Insights from an Australian study of criminal law-making. (July 2021) - McNamara, Luke; Quilter, Julia; Hogg, Russell; Loughnan, Arlie; Douglas, Heather; Brown, David; Farmer, Lindsay
Criminalisation theory scholars have examined important questions regarding what behaviours should be criminalised and why . More recently, greater attention has been paid to linking normative accounts with empirical and historicised analyses of criminalisation practices. Building on recent work on modalities of criminalisation as a methodological tool for contextual criminalisation research, this article introduces a second analytical approach for better understanding how criminal laws are made: processes of criminalisation. We discuss the findings of a pilot study of 143 criminal law statutes enacted in three Australian jurisdictions (New South Wales, Queensland, Victoria) from 2012–2017. We conclude that a processes approach supports a nuanced appreciation of the conditions under which criminal law statutes are produced, and facilitates scrutiny of whether legislative enactments are evidence-based and a product of meaningful consultation and genuine democratic participation in law-making.